2016
DOI: 10.4236/jbnb.2016.74018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nanodiamonds at the Action of Colored Metal Ions on the Skin of Guinea Pigs

Abstract: The protective effect of modified nanodiamonds (MND) under the action of cobalt and nickel ions on the skin of Guinea pigs was shown. At the action of chromium ions on the skin of animals, the protective effect of MND was not found. The differences are related to different adsorption properties of MND to the investigated colored metal ions. It is shown in vitro that MND can adsorb ions of cobalt and nickel and don't bind ions of chromium from aqueous medium. The perspectives using of MND as a new drug for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Additionally, no adverse effects have been observed in several in vivo experiments [ 11 , 12 ]. FNDs were, for instance, used for drug delivery in animal models like mice [ 13 ], fruit flies, worms, or pigs [ 14 ]. Chow et al showed that the nanodiamond drug delivery system improved both drug retention in tumour cells and treatment safety and efficacy in murine cancer models for tumour treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no adverse effects have been observed in several in vivo experiments [ 11 , 12 ]. FNDs were, for instance, used for drug delivery in animal models like mice [ 13 ], fruit flies, worms, or pigs [ 14 ]. Chow et al showed that the nanodiamond drug delivery system improved both drug retention in tumour cells and treatment safety and efficacy in murine cancer models for tumour treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…S7) of Co-MOF and Ni-MOF show broad peaks centered at around 524 and 395 nm, respectively, which arise due to the d–d transition and these peak positions are consistent with the octahedral coordination sphere. 39,40 A regular increase in the intensity of the 524 nm band on increasing the mole ratio of Co and similarly a regular increase in the intensity of the 395 nm band on increasing the mole ratio of Ni are distinctly observed. These results match well with the ratio of starting precursors and EDAX data.…”
Section: Resultsmentioning
confidence: 75%
“…Moreover, prolonged exposure to modified nanodiamonds exerts a protective effect on the skin of guinea pigs treated with nickel and cobalt ions. This reduces the probability of an allergic reaction, which often occurs as a result of irritation [ 16 , 53 ]. However, the comparison between human and mouse skin tissue highlights the presence of significant species differences, emphasizing the importance of considering these variations when utilizing mice as a substitute model for understanding human physiology [ 54 ].…”
Section: Discussionmentioning
confidence: 99%